Factors determining the adoption of energy-saving technologies in Swiss firms: An analysis based on micro data - Spyros Arvanitis; Marius Ley (ETH Zurich, KOF Swiss Economic Institute, 2010)
This study investigates the factors that determine the inter-firm and intra-firm adoption rates of energy-saving technologies. These factors can be on theoretical terms firm-specific rank effects, inducement effects, adoption barriers as well as order, stock and epidemic effects that are related to different kinds of external effects. Data for 2324 Swiss firms for the year 2008 are used that contain information about four categories of energy-saving technology applications (electromechanical and electronic applications; applications in motor vehicle and traffic engineering; in building construction; and in power-generating processes) that are studied separately. The results show that there are significant differences with respect to rank effects and adoption barriers between inter-and intra-firm diffusion. In practically all cases positive epidemic and/or network effects outweigh potential negative stock and order effects. Inducement effects, particularly those traced back to intrinsic motivations for environmentfriendly technologies, show clearly positive effects on the adoption rates.
Keywords: O31; O33; 330; energy-saving technologies; technology adoption; Energiesparen; Technologiewahl; Innovation; Schweiz